2020
DOI: 10.1002/ijc.33107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tRNA‐derived fragments and human cancers

Abstract: tRNA-derived fragments, a class of small noncoding RNAs (sncRNAs), have been identified in numerous studies in recent years. tRNA-derived fragments are classified into two main groups, including tRNA halves (tiRNAs) and tRNA-derived small RNA fragments (tRFs), according to different cleavage positions of the precursor or mature tRNAs. Instead of random tRNA degradation debris, a growing body of evidence has shown that tRNA-derived fragments are precise products of specific tRNA modifications and play important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 95 publications
(212 reference statements)
0
40
0
Order By: Relevance
“…Both subtypes of tsRNA are closely related to the development of tumors [14,20,21]. For example, specific tRFs derived from tRNA-Glu, tRNA-Asp, tRNA-Gly, and tRNA-Tyr suppress breast cancer by binding to Y box binding protein 1 (YBX1) and destabilizing oncogenic transcripts [22].…”
Section: Introductionmentioning
confidence: 99%
“…Both subtypes of tsRNA are closely related to the development of tumors [14,20,21]. For example, specific tRFs derived from tRNA-Glu, tRNA-Asp, tRNA-Gly, and tRNA-Tyr suppress breast cancer by binding to Y box binding protein 1 (YBX1) and destabilizing oncogenic transcripts [22].…”
Section: Introductionmentioning
confidence: 99%
“…5′-tRF-Lys TTT , 5′-tRF-Val CAC , 5′-tRF-Glu CTC , 5′-tRF-Pro CGG tRF-5 Associate with chemotherapy treatment outcomes [26] prostate cancer tRF-1001 tRF-1 TRF-1001 is required for cell proliferation. [31] tRNA Lys-CTT tRNA Phe-GAA tRF The ratio of tRFs derived from tRNA Lys-CTT and tRNA Phe-GAA is a good indicator of progression-free survival.…”
Section: Mechanisms Of Breast Cancer Resistance Related To Trfs and Tmentioning
confidence: 99%
“…These two mutations are involved in the resistance of breast cancer cells to lapatinib. [26] lung cancer tRF-Leu-CAG tRF-Leu-CAG may be related to AURKA. AURKA overexpression induces gefitinib and cisplatin resistance.…”
Section: Mechanisms Of Breast Cancer Resistance Related To Trfs and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the underlying mechanism of tRF regulates various human diseases such as cancers, pathological stress injuries, metabolic diseases, viral infections, and nervous system diseases [14][15][16]. However, the understanding of how tRF regulates cancer progression is still in its infancy [17].…”
Section: Introductionmentioning
confidence: 99%